Energy Expended Playing Nintendo Wii. - Forde, Cuisle; O'Donovan, C.; Hussey, J. (My University, 2011)
The Wii is a video game console on which activity video games can be played. These games require players to be physically active. Despite their popularity and widespread use, it is not known if players reach the intensity of exercise advised for cardiovascular benefits when playing these games. The American College of Sports Medicine recommends that adults participate in at least 30 minutes of moderate activity on five or more days of the week. Moderate intensity exercise is that which results in an energy expenditure of between 3 and 6 metabolic equivalents (METs), or above 55% of maximal heart rate.
WCPT Congress Conference Proceedings
Keywords: Nintendo Wii; Physical activity; Energy expenditure; Computer & Video Games; ENERGY-EXPENDITURE; EXERCISE; PHYSICAL ACTIVITY; Children; Health; Sports